Stereoselective Convergent Synthesis of Carbon Skeleton of Cotylenin A Aglycone - Kuwabara, Motoi; Matsuo, Ami; Kamo, Shogo; Matsuzawa, Akinobu; Sugita, Kazuyuki (Synthesis, 2021)
In this paper, the synthesis of the carbon skeleton of cotylenin A aglycone is described. The key reactions, including an intramolecular aldol reaction, an aldol coupling reaction, and a ring-closing metathesis, allow for the effective and stereoselective access to the carbon skeleton of cotylenin A aglycone. The stereochemistry was confirmed by single-crystal X-ray crystallographic analyses of related compounds.
Keywords: cotylenin A; cotylenol; carbocycles; polycycles; natural products; ring-closing metathesis